Environmental Scanning in Globally Oriented Small Businesses:: Practices Suggested by Managers - Nkongolo-Bakenda, Jean-Marie (Journal of Comparative International Management, 2003)
This paper identifies information sources and practices of environmental scanning preferred by managers of globally oriented small and medium-sized enterprises (GOSMEs). Data were collected using a Delphi technique and were analysed by NUD*IST software and the Homogeneity Analysis technique. Major findings indicate that although managers of GOSMEs generally prefer external and personal sources in their environment scanning process, contingent conditions related to the industry, the organization and the owner-manager guide the choice of appropriate information source and the need to scan systematically each sector of the environment. Statistical relationships were identified, and these relationships allowed the formulation of general propositions that could be helpful for practice and research in GOSMEs. The paper concludes that the manager's need to scan systematically a specific sector of the environment and the information source the firm might use are dependent on the level of uncertainty aroused by this sector, the amount of pertinent information the source has, and its accessibility by the firm.